Is large good enough? Evaluating and improving representation of ecoregions and habitat types in the European Union's protected area network Natura 2000. (November 2018) - Müller, Anke; Schneider, Uwe A.; Jantke, Kerstin
Abstract: Natura 2000, the largest protected area network worldwide, covers 18.2% of the European Union's terrestrial area. Thereby, the network surpasses the goal of the Convention on Biological Diversity's Aichi target 11 to protect 17% of the land area by 2020. However, Aichi target 11 also calls for protected area networks to be ecologically representative. Here, we analyzed the coverage of 43 ecoregions in the terrestrial Natura 2000 estate. To simulate cost-efficient closing of gaps in the current system, we applied a linear programming model that solves the minimum set conservation problem of expanding the Natura 2000 network to achieve 10% ecoregion representation. As Natura 2000 sites are designated for habitat types and species listed on the annexes of the Habitats and Birds directives, we included 226 habitat types as a further biodiversity surrogate in the optimization. We found six ecoregions that currently do not meet the 10% representation target. To close these gaps, an additional 15, 187 km 2 (0.35% of the European Union's land territory) would be required. Simultaneously, representation of 21 habitat types could be increased. The United Kingdom would have to contribute more than half of the additional area, followed by Estonia, Latvia, France, and Italy. To protect biodiversity effectively and to comply with international conservation targets such as Aichi target 11, we recommend continuous evaluation and improvement also of already well-established protected area networks. Highlights: We evaluate representation of ecoregions and habitat types in Natura 2000. We suggest a cost-efficient expansion of Natura 2000 to improve representation. For six current gap ecoregions total additional conservation area of 15, 187 km 2 is required. Simultaneously representation of habitat types can be slightly increased. The additional conservation area is distributed across 11 EU member states.